Knock Control in a Diesel-Dual-Fuel Premixed-ChargeCompression-Ignition (DF-PCCI) Engine Using a Fuzzy Supervisory System - Yaovaja, Kittipong; Chatlatanagulchai, Withit (Agriculture and Natural Resources, 2014)
Typical diesel-dual-fuel (DDF) engines have compressed natural gas (CNG) injected into the intake ports as the main fuel and diesel injected into the cylinders for ignition. Recently, a new DDF combustion technology, developed and patented by the PTT Public Company Limited, advanced the diesel injection timing to be early in the compression stroke, resulting in higher energy replacement by the CNG and lower emissions than those of typical DDF engines. In the so-called diesel-dual-fuel premixed-charge-compression-ignition (DF-PCCI) engine, the diesel, CNG and air were mixed together during the compression stroke. Auto-ignition could occur at many places in the mixture; therefore, the combustion process was more sudden and violent. The engine experienced heavy knocking at high loads due to the hotter combustion chamber as well as hard combustion during transient stages due to the high in-cylinder pressure gradient. Without knock control, the engine had to be operated conservatively away from the knock threshold and not at its optimum point. This paper presents a novel knock control algorithm using a fuzzy supervisory system. The work progressed with the following steps. First, the knock intensity was measured on-line in a time-domain for each cylinder with one knock sensor per engine. Second, a knock threshold was selected from correlating the knock intensity of the DF-PCCI engine with that of the diesel engine. Third, several factors that affected knock intensity were identified. Fourth, standard fuzzy controllers were used to adjust the set points of those factors to regulate the knock intensity at the knock threshold. Each cylinder was treated separately. Fifth, fuzzy supervisors were used to determine the amount of each factor to be applied at each operating point by adjusting the output gains of the standard fuzzy controllers. Sixth, a DF-PCCI engine, mounted on an engine dynamometer, ran the NEDC test with on-line emissions measurement. Seventh, performance (torque and drivability), efficiency (the amount of CNG that can replace diesel) and emissions (total hydrocarbon emissions, NOx, CO, and CH4) were compared with and without knock control. The results showed very good performance with improvements in drivability, efficiency and NOx emission when the proposed knock control algorithm was applied.